Influência da ventilação natural na sensação térmica do usuário em ambiente educacional - Almeida, Patryck Machado de (2019)
The increase in energy consumption is a theme that has aroused a wide concern of many researchers and authorities in almost all the world, and one of the factors that influence this consumption is the increasing in the use of artificial acclimatization systems, mainly air conditioners. Thus, the search for buildings that demand less energy has become increasingly common in the last years. Therefore, the use of natural ventilation stands out as an important strategy to promote thermal comfort and indoor air quality, with minimal or no energy consumption at all. The research evaluated the hygrothermal conditions and the air movement acceptability as a comfort strategy in a naturally ventilated educational environment in the city of Vitória / ES, which climate is classified as tropical hot and humid. It also verified the influence of the ventilation on the comfort of the users and the impact of prior exposure of users to conditioned environments in their thermal preference. For this, measurements of the internal environmental variables (air temperature, globe temperature, relative air humidity and air velocity) were carried out while the occupants answered the questionnaire regarding thermal sensations and air velocity. In this way, the associations between the values of the environmental variables and the sensations reported by the occupants were obtained. The results are presented in the form of tables and graphs by relating the internal microclimatic variables with the occupants' responses. The results demonstrated that the highest values of thermal neutrality were concentrated with the operating temperature between 26 °C and 28 °C. The occupants, for the most part, accepted air velocities above 1m/s, mainly from 26ºC, and these were fundamental in reducing thermal discomfort by heat. There were differences between the thermal preference of occupants with and without the routine exposure to air conditioned environments. Regarding the type of acclimatization in the environment studied, 53.6% of users answered that they prefer natural ventilation, while 26.8% prefer natural ventilation and fans and 19.6% opted for air conditioning.